2002
DOI: 10.1111/1467-9450.00269
|View full text |Cite
|
Sign up to set email alerts
|

Temperament in children with Down syndrome and in prematurely born children

Abstract: Parents of three groups of children completed the Children's Behavior Questionnaire (CBQ). Participants were children with Down syndrome aged 4-11 years (n = 55), prematurely born children aged 5 years (n = 97), and a group of normally developing kindergarten children 5-7 years of age (n = 91). Mean levels and factor structures on the CBQ were compared between the three groups. The children with Down syndrome had less attentional focusing and expressed less inhibitory control and less sadness than the normally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 45 publications
(93 reference statements)
1
31
0
1
Order By: Relevance
“…In addition, lower Negative Emotionality for infants with DS observed in this study supports the idea that lower levels of reactivity, related to decreased noradrenergic and adrenergic activity, may translate into fewer negative emotional responses for infants with DS. The latter finding also lends support to the results reported by Nygaard et al (2002), indicating that children with DS showed lower levels of sadness. On the other hand, results of this study conflict with findings reported by Bridges and Cicchetti (1982), Ohr andFagen (1993), andRatekin (1996), most likely as a function of different assessment approaches and ages of included children with DS.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, lower Negative Emotionality for infants with DS observed in this study supports the idea that lower levels of reactivity, related to decreased noradrenergic and adrenergic activity, may translate into fewer negative emotional responses for infants with DS. The latter finding also lends support to the results reported by Nygaard et al (2002), indicating that children with DS showed lower levels of sadness. On the other hand, results of this study conflict with findings reported by Bridges and Cicchetti (1982), Ohr andFagen (1993), andRatekin (1996), most likely as a function of different assessment approaches and ages of included children with DS.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, Bridges and Cicchetti (1982) utilized a different parent-report instrument, the Infant Temperament Questionnaire (ITQ; Carey 1970), and relied on the normative sample (3.5-8.5 months of age) utilized in the development of this questionnaire as a comparison group. Research conducted by Ratekin (1996) and Nygaard et al, (2002) was based on samples of school-age children, utilizing different parent-report assessment tools.For the current study, it was hypothesized that previous finding demonstrating significant differences in temperament manifestations (e.g., duration of orientating, smiling/laughter, and vocal reactivity) between children with DS and comparison youngsters would be replicated. Specifically, because of the similarity in the approach to the measurement of temperament and age ranges, we expected to replicate the findings of Rothbart & Hanson (1983), expanding on this earlier investigation by examining additional domains of temperament (e.g., Perceptual Sensitivity, Falling Reactivity, Cuddliness/Affiliativeness).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to typically developing controls, children with ASD have been rated as significantly lower on effortful control, with particular difficulties focusing attention, shifting attention, and inhibiting prepotent responses (Janes 2001;Konstantareas and Stewart 2006;Landry 2000). Such problems have been reported in other developmentally-delayed populations (Nygaard et al 2002), raising questions about the role of intellectual impairment, as typically found in ASD (Fombonne 2005). However, effortful control is reportedly more problematic in children with ASD than developmentally-matched children with Down syndrome (Landry 2000), consistent with higher rates of executive dysfunction in ASD than in other forms of developmental psychopathology (Hill 2004).…”
Section: Temperament and Asdmentioning
confidence: 90%
“…Even when presented with fearful expressions in caregivers, DS children do not show fear and respond with a generally positive affect (Knieps et al, 1994). DS children show less behavioral inhibition (Nygaard et al, 2002) and more impulsivity and compulsive behaviors (Kopp et al, 1983;Evans and Gray, 2000). These behaviorsFimpulsivity and lack of fearFare one extreme of the harm avoidant dimension of Cloninger's Tridimensional theory of personality (Cloninger, 1987).…”
Section: Discussionmentioning
confidence: 99%